2016
DOI: 10.18632/oncotarget.13342
|View full text |Cite|
|
Sign up to set email alerts
|

Adipocytes secreted leptin is a pro-tumor factor for survival of multiple myeloma under chemotherapy

Abstract: Accumulating evidences have shown that adipokines secreted from adipocytes contributes to tumor development, especially leptin. However, underlying mechanisms remain unclear. This study aims to explore the effect of leptin on development and chemoresistance in multiple myeloma cells and the potential mechanism. Analysis of levels of adipokines including leptin and adiponectin in 28 multiple myeloma patients identified significantly higher leptin compared with 28 normal controls(P < 0.05), and leptin level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 31 publications
6
48
0
3
Order By: Relevance
“…Anti-apoptotic effect of leptin in cancer is a frequent observation of many investigators [181185]. Similarly, several reports have documented that leptin can facilitate the formation of new blood vessels or angiogenesis, along with biosynthesis of pro-angiogenic factors like VEGF [185187].…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%
“…Anti-apoptotic effect of leptin in cancer is a frequent observation of many investigators [181185]. Similarly, several reports have documented that leptin can facilitate the formation of new blood vessels or angiogenesis, along with biosynthesis of pro-angiogenic factors like VEGF [185187].…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%
“…Other researchers later confirmed that leptin induces myeloma proliferation. For example, in one study researchers analyzed levels of adipokines including leptin and adiponectin in 28 MM patients and identified significantly higher leptin compared with controls [23]. Leptin levels were positively correlated with clinical stage, bone marrow plasma cells percentage, and levels of immunoglobulin G (IgG), beta-2 microglobulin (β2MG), and erythrocyte sedimentation rate [23].…”
Section: Mat Adipokines Lipids and Cell-cell Contact Supports Camentioning
confidence: 99%
“…For example, in one study researchers analyzed levels of adipokines including leptin and adiponectin in 28 MM patients and identified significantly higher leptin compared with controls [23]. Leptin levels were positively correlated with clinical stage, bone marrow plasma cells percentage, and levels of immunoglobulin G (IgG), beta-2 microglobulin (β2MG), and erythrocyte sedimentation rate [23]. In MM cell and adipocyte co-culture, increased growth of myeloma cells and reduced toxicity of bortezomib were observed, along with increased expression of cyclinD1, B-cell lymphoma 2 (Bcl-2) and decreased caspase-3 expression.…”
Section: Mat Adipokines Lipids and Cell-cell Contact Supports Camentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloma is the second most common hematological malignancy worldwide, affecting nearly 100,000 people in the United States alone, and remains incurable [2, 3]. The bone marrow microenvironment (BMME), an intricate and dynamic niche composed of extracellular matrix (ECM) proteins and cells of hematopoietic lineage, serves as an instrumental contributor to myeloma disease progression [4].…”
Section: Introductionmentioning
confidence: 99%